2014
DOI: 10.3389/fmicb.2014.00006
|View full text |Cite
|
Sign up to set email alerts
|

Blood dendritic cells: “canary in the coal mine” to predict chronic inflammatory disease?

Abstract: The majority of risk factors for chronic inflammatory diseases are unknown. This makes personalized medicine for assessment, prognosis, and choice of therapy very difficult. It is becoming increasingly clear, however, that low-grade subclinical infections may be an underlying cause of many chronic inflammatory diseases and thus may contribute to secondary outcomes (e.g., cancer). Many diseases are now categorized as inflammatory-mediated diseases that stem from a dysregulation in host immunity. There is a grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 163 publications
2
21
0
2
Order By: Relevance
“…DCs have been shown to continuously present endogenous antigens and prime the T-cell response in inflammatory conditions (Leung et al, 2002;Eriksson et al, 2003;Bailey et al, 2007). The role of DCs in the pathogenesis of autoimmune disease, such as RA, has been confirmed in numerous studies (Pulendran et al, 2010;Rodríguez-Fernández, 2013;Miles et al, 2014). Studies have demonstrated that the infiltrated DCs in the inflamed synovial tissue subsequently migrate to the draining lymph nodes and present arthritogenic peptide to T cells and induce naive T-cell activation (Pettit et al, 2000;Lutzky et al, 2007).…”
Section: Introductionmentioning
confidence: 96%
“…DCs have been shown to continuously present endogenous antigens and prime the T-cell response in inflammatory conditions (Leung et al, 2002;Eriksson et al, 2003;Bailey et al, 2007). The role of DCs in the pathogenesis of autoimmune disease, such as RA, has been confirmed in numerous studies (Pulendran et al, 2010;Rodríguez-Fernández, 2013;Miles et al, 2014). Studies have demonstrated that the infiltrated DCs in the inflamed synovial tissue subsequently migrate to the draining lymph nodes and present arthritogenic peptide to T cells and induce naive T-cell activation (Pettit et al, 2000;Lutzky et al, 2007).…”
Section: Introductionmentioning
confidence: 96%
“…annotine. As DCs are the most potent professional antigen-presenting cells and can have a major effects on T cell responses they are attractive targets for clinical therapies targeting autoimmune diseases and chronic infections (Miles et al 2014). We, therefore, used DCs and co-cultures of DCs and T cells to study the potential of annotine to affect DC activation and how annotine-treated DCs modulate T cell responses.…”
Section: Introductionmentioning
confidence: 99%
“…DCs present antigens to T cells and induce T cell activation in inflammatory conditions [21][22][23] . It has been reported in numerous studies that DCs play important role in the pathogenesis of autoimmune disease such as RA [24][25][26] . The infiltrated DCs migrate from the inflamed synovium to the draining lymph nodes, present arthritogenic peptide to T cells and activate T cells [27,28] .…”
Section: Research Highlightmentioning
confidence: 99%